2013
DOI: 10.1111/mec.12285
|View full text |Cite
|
Sign up to set email alerts
|

Paths to selection on life history loci in different natural environments across the native range of Arabidopsis thaliana

Abstract: Selection on quantitative trait loci (QTL) may vary among natural environments due to differences in the genetic architecture of traits, environment-specific allelic effects or changes in the direction and magnitude of selection on specific traits. To dissect the environmental differences in selection on life history QTL across climatic regions, we grew a panel of interconnected recombinant inbred lines (RILs) of Arabidopsis thaliana in four field sites across its native European range. For each environment, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 90 publications
(170 reference statements)
10
127
0
Order By: Relevance
“…In conclusion, early life stages are known to be under strong selection (15)(16)(17)(18)(19) and to have cascading effects across the whole life cycle (16,20,21), but they are seldom included in studies on the genetic basis of local adaptation (12)(13)(14)(22)(23)(24)(25)(26)(27)(28). By conducting a reciprocal transplant experiment including the whole life cycle and maternal effects, we have shown that selection during early life stages contributes strongly to both the magnitude and the genetic basis of adaptive differentiation among natural populations of A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, early life stages are known to be under strong selection (15)(16)(17)(18)(19) and to have cascading effects across the whole life cycle (16,20,21), but they are seldom included in studies on the genetic basis of local adaptation (12)(13)(14)(22)(23)(24)(25)(26)(27)(28). By conducting a reciprocal transplant experiment including the whole life cycle and maternal effects, we have shown that selection during early life stages contributes strongly to both the magnitude and the genetic basis of adaptive differentiation among natural populations of A. thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, field experiments with plants are usually based on the transplantation of seedlings (12)(13)(14)(22)(23)(24)(25)(26)(27)(28) and therefore do not assess the importance of possible adaptive differentiation and genetic tradeoffs expressed at the seed and germination stage. Indirect evidence suggests that the seed stage may contribute considerably to local adaptation.…”
mentioning
confidence: 99%
“…We did not directly estimate a fitness proxy such as seed set, but we reasoned that traits shown to have adaptive value in A. thaliana, such as flowering time (87)(88)(89), will be subject to evolutionary forces comparable to those acting directly on fitness. Although flowering time is locally adaptive in A. thaliana, the correlation between flowering time and fitness varies by accession and environment (90)(91)(92). Large-effect mutations in flowering time genes can significantly perturb fitness, but their effect is not directional and varies by genetic background (90,93), providing one possible explanation for variable correlation between these two traits.…”
Section: Arabidopsis Thaliana In the Context Of Traditional Heterosismentioning
confidence: 99%
“…Most remarkable, though, seems the negligible role of FLC in the adjustment of flowering time along altitude. While MAF2 and MAF3 are known to vary extensively among natural populations (Caicedo et al, 2009;Rosloski et al, 2010) and have repeatedly been identified as important flowering time regulators in quantitative trait locus analyses using wild accessions (Salomé et al, 2011;Silady et al, 2011;Lasky et al, 2012;Fournier-Level et al, 2013;Grillo et al, 2013), the evolutionary properties of AGL19 and its distribution among natural populations will need further investigation.…”
Section: Gene Expression and Altitudementioning
confidence: 99%
“…For example, AGL19 has been found to promote flowering following vernalization without interacting with FLC (Schönrock et al, 2006), and relatives of FLC, the MADS AFFECTING FLOWERING genes (MAF1-MAF5; MAF1 is also referred to as FLOWERING LOCUS M [FLM]; De Bodt et al, 2003), have been shown to inhibit flowering in a similar way to FLC (Ratcliffe et al, 2003;Scortecci et al, 2003;Werner et al, 2005;Sung et al, 2006;Gu et al, 2013). Genes MAF2 to MAF5 (Ratcliffe et al, 2003) are arranged in a tandem gene array and vary extensively among natural populations (Caicedo et al, 2009;Rosloski et al, 2010), and several recent studies have associated this polymorphic region with natural variation in flowering time (Salomé et al, 2011;Silady et al, 2011;Lasky et al, 2012;Fournier-Level et al, 2013;Grillo et al, 2013), making these genes interesting candidates for studying associations between flowering time and ecological parameters.…”
mentioning
confidence: 99%